A renewable wood-derived cathode for Li–O2 batteries. Issue 29 (10th July 2018) - Zhu, Chunliang; Du, Li; Luo, Junming; Tang, Haibo; Cui, Zhiming; Song, Huiyu; Liao, Shijun
Abstract : In this work, we developed a renewable wood-derived cathode with well-aligned elongated microchannels for high-performance Li–O2 batteries. Abstract : In this work, we developed a renewable wood-derived cathode with well-aligned elongated microchannels for high-performance Li–O2 batteries. The cathode was obtained from natural wood following carbonization, activation, and then loading of RuO2 nanoparticles (4.15 wt%) as catalysts (RuO2 /WD-C). The cathode has a three-dimensional, high stability carbon matrix, uniformly anchored catalysts, and well-aligned porous microchannels. As a result, the specific areal capacity of the assembled batteries exceeds 8 mA h cm −2 and the charge terminal potential is lower than 3.8 V at 0.1 mA cm −2 . The energy efficiency was improved up to 91.9% and exceeded 87.1% after 100 cycles (curtailed capacity of 0.5 mA h cm −2 at 0.2 mA cm −2 ). Furthermore, the RuO2 /WD-C cathode can be fully regenerated from a deep discharge–charge cycle or 100 curtailed-capacity cycles by simply washing with water. The areal capacity of the regenerated RuO2 /WD-C cathode is comparable to the performance of the initial cathode. The cut-off voltage was above 2.6 V following 200 cycles. Even when regenerated for the second time, the RuO2 /WD-C cathode still demonstrated almost the same high performance as the initial one, indicating its high stability and excellent renewability.